THE IMPACT OF RELEVANT FACTORS ON WHEAT SUPPLY AND DEMAND IN THE REPUBLIC OF SERBIA - Ignjatijević, Svetlana; Čavlin, Miroslav; Jahić, Miralem (Economics of Agriculture, 2018)
The aim of the study is to conduct the wheat balances analysis, to research the supply and demand in the domestic market, and to examine the partial impact of the relevant factors on the supply and demand. The the research results of wheat production and trade flows can contribute to the increase of supply and to the structural changes in production, the strengthening of competitiveness, the increase of trade exchange, improvement in production and processing, new investments, higher employment rate, and so on. The methods used in the research are the wheat balances analysis, the functional and correlation analysis (the functional correlation analysis), the variance analysis, T-test, as well as other general methods. The results of the wheat production and consumption balances analysis indicate the existence of surplus and potential for export of an average of 805.29 thousand tons with a trend of increase after 2013. The impact of production, initial stocks, imports, and purchase prices on wheat supply is high (R = 0.99). The impact of consumption, sales prices, income, exports, and final stocks on wheat demand is high (R = 0.95). By analyzing the correlation coefficient of wheat production and supply, a coefficient of 0.96 was obtained, while for the wheat consumption and demand the obtained coefficient was 0.82, which indicates high correlation dependence. In the period 2000-2016, the export of wheat was increased 8.7 times along with the increase in price per kg and the total export value.